Between continuity and paradigm shift: Pension reforms in Germany - Karl Hinrichs (Universität Bremen, Zentrum für Sozialpolitik (ZeS), 2003)
In general, the policy domain of old-age pensions is characterized by institutional continuity and only incremental reforms. Since the late 1980s, in Germany a series of public pension reforms, all initiated in view of imminent population aging, have happened. In this paper it is looked into the process and content of reforms legislated between 1989 and 2001 in order to understand the nature of change and its driving forces. The main question to be answered is whether these single reform steps eventually amounted to a 'path departure'. Despite the reforms the public pension scheme will continue to be the central component of retirement income for the next decades to come, and traditional features of that social insurance program remained intact. However, it can no longer be regarded as a coherent and undisputed policy paradigm: pension politics has become increasingly conflictuous, and the scope of policy-making has widened from public pension policy (parametric reforms concerning a tighter contribution-benefit link, prolonged working life, adjustment formulae etc.) to retirement income policy. Thereby some of the public scheme's established principles have been abandoned, non-public components of retirement income are pushed and new actors become involved in the politics of pensions. It is thus justified to speak of a paradigmatic change that has occurred.
Keywords: 300